Effectiveness of Virtual Reality-based Rehabilitation and High-intensity Exercise Program for Total Knee Arthroplasty Patients: A Randomised Controlled Trial - K Nishitha; A Anitha; D Thaheera (Journal of Clinical and Diagnostic Research)
Introduction: Progression of articular cartilage loss and wear and strain are the usual causes of Osteoarthritis (OA), sometimes referred to as degenerative joint disease. India had roughly 200,000 knee arthroplasty procedures in 2020 in which nearly 72% were because of OA. Rebuilding the knee joint through knee arthroplasty is a great alternative for treating symptomatic OA in patients who have not responded to conservative treatment. Aim: To determine the effect of Virtual Reality (VR)- based rehabilitation and high-intensity exercise program for Total Knee Arthroplasty (TKA). Materials and Methods: In this double-blinded randomised controlled trial, 36 participants matched the inclusion criteria who underwent Total Knee Replacement (TKR) at the Department of Physiotherapy, Saveetha College of Physiotherapy, SIMATS, Chennai, Tamil Nadu, India. The study was started in the month of October 2023 and ended in January 2024. Then the participants were randomly allotted to an experimental group-VR (n=18) and a conventional group-high-intensity exercises (n=18). Outcome measures used are the Numeric Pain Rating Scale (NPRS) pain scale, knee range of motion, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Timed Up and Go (TUG) test. A paired t-test was utilised to evaluate significant variations between the pre- and post-test measurements. In order to find any meaningful differences between the two groups, an unpaired t-test was employed. Result: The average mean±Standard Deviation (SD) of age and Body Mass Index (BMI) was found to be 51.2±5.2 yearsand 28.3±2.0 kg/m². The experimental group and the conventional group both exhibited notable changes in terms of within-group differences. Numeric Pain Rating Scale (NPRS) significantly showed the same between the groups, but the range of motion showed better output in VR-based rehabilitation than indifferently supporting the pain outcome of the experimental group (p≥0.0001). Balance, gait and functional activities were improved in the experimental group compared to the conventional group and in the VR-based rehabilitation, the functional independence of the patient was achieved in nine weeks compared to the High-intensity (HI) exercises. Conclusion: The VR-based rehabilitation showed better outcomes in pain, range of motion, balance, gait and functional independence than a high-intensity exercise programme.